2003
DOI: 10.1037/0022-0663.95.4.719
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Individual Differences in Reading Comprehension and Reading Fluency.

Abstract: This study examined the common and distinct contributions of context-free and context reading skill to reading comprehension and the contributions of context-free reading skill and reading comprehension to context fluency. The 113 4th-grade participants were measured in reading comprehension, read aloud a folktale, and read aloud the folktale's words in a random list. Fluency was scaled as speed (words read correctly in 1 min) and time (seconds per correct word). Relative to list fluency, context fluency was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

37
342
2
20

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 424 publications
(401 citation statements)
references
References 65 publications
37
342
2
20
Order By: Relevance
“…This presumption will need to be supported by further research. To sum up, similarly to Jenkins et al (2003), we can state that no matter if the decoding is measured by reading isolated words or words in context, the deficiency of children with dyslexia is always visible.…”
Section: Decoding Skillsmentioning
confidence: 99%
See 1 more Smart Citation
“…This presumption will need to be supported by further research. To sum up, similarly to Jenkins et al (2003), we can state that no matter if the decoding is measured by reading isolated words or words in context, the deficiency of children with dyslexia is always visible.…”
Section: Decoding Skillsmentioning
confidence: 99%
“…Nicholson, 1991;Jenkins et al, 2003;Ardoin et al, 2013). If we take into consideration the number of words read within the oneminute time limit, these studies mention higher test scores for reading words in context for both beginners and advanced readers (Nicholson, 1991;Jenkins et al, 2003).…”
Section: Decoding Skillsmentioning
confidence: 99%
“…rapid automatized letters naming, grapheme-phoneme connections, phonemic blending, decoding non-sense words, decoding words in disconnected and connected text). Jenkins et al (2003) analyzed the relationships between the levels of RF to reading comprehension and found that RF in connected text is the best predictor for reading comprehension, accounting for 41% of unique variance above reading fluency of words in disconnected text. The outcome of their research is consistent with other studies that found the ability to read fluently a connected text to account for most of the variance in predicting proficiency in reading comprehension, compared with reading fluently words in disconnected texts in the native language (L1) (e.g.…”
Section: Levels Of Rfmentioning
confidence: 99%
“…Cutting & Scarborough, 2006;Caravolas, Volín, & Hulme, 2005). Recently, the unique contribution of word reading in and out of the context has also been discussed (Jenkins, Fuchs, van den Broek, Espin, & Deno, 2003;Ardoin et al, 2013). …”
Section: Introductionmentioning
confidence: 99%